Effects of Power Split Ratio and Optical Delay Phase Tuning on Stabilization of Self-Mode-Locked Quantum-Dash Lasers Subject to Dual-Loop Optical Feedback - Haroon Asghar; John G. McInerney (IEEE Photonics Journal, 2020)
In the present work, we report a path of RF stabilization versus delay subject to self-mode-locked (SML) two-section quantum-dash (QDash) lasers emitting at ∼1.55 μm and operating at ∼21 GHz repetition rate using a feedback ratio controlled and optical delay phase-dependent symmetric dual-loop optical feedback. For symmetric dual-loops (equal arms of external loops), we identify the three key parameters: power-split ratio through each cavity of the external feedback loop, optical delay phase settings, and overall feedback strength back into gain section, yields jitter stabilization on integer resonance as well as on full delay range tuning. Symmetric dual-loop feedback with two optical delay phase settings (weaker cavity set to integer resonance, fine-tuning of the stronger cavity and stronger cavity set to integer resonance, fine-tuning of a weaker cavity) and four chosen combinations of feedback ratios (−19.5:−29.03 dB, −20.6:−24.3 dB, −21:−22.7 dB, −21.3:−23 dB) has been demonstrated. Based on these four chosen combinations of feedback ratios and optical delay phase settings, a path of stabilization has been identified for SML QDash lasers using symmetric dual-loop optical feedback. Our proposed dual-loop feedback schemes provide a viable path towards the stabilization of mode-locked lasers, promising for various practical applications where ultra-stable optical pulses are highly desirable.